(untitled) (Journal of Lumbini Medical College, 2020)
Introduction: Salivary gland tumor accounts for about 5% of all the neoplasms of the head and neck. 75% of such tumors occur in the parotid glands. Pleomorphic adenoma is the most common type of benign salivary gland tumor. It tends to recur after inappropriate treatment. Surgery of parotid tumor includes enucleation, superficial parotidectomy and total parotidectomy. Identification and preservation of facial nerve trunk and its branches is very important in parotid surgery. Advancement of microsurgical technique has helped in better visualization, identification and preservation of the facial nerve. Methods: This prospective study included twenty-seven patients. Preoperative ultrasonography and fine needle aspiration cytology were done for all cases. Computed tomography/magnetic resonance imaging were performed in some cases when needed. Standard microsurgical technique with the help of microscope was performed for antegrade parotidectomy. Data analysis was done using SPSS version 26.0. Results: The patients age ranged from 12 to 78 years. Fifteen (55.6%) patients were female and 12 (44. 4%) were males. Sixteen (59.3%) tumors were located on the right side whereas 11 (40.7%) were on the left side. Most of the tumors (n=18, 66.7%) were pleomorphic adenoma. Two (7.4%) of the patients had temporary facial paralysis which improved with time. Two (7.4%) patients had developed hematoma. Frey’s syndrome was not found in follow-up. Conclusion: This study showed low morbidity in parotidectomy using microsurgical techniques. No permanent injury to the facial nerve was found.